PENGARUH MODEL MAKE A MATCH TERHADAP MOTIVASI BELAJAR BAHASA INDONESIA SISWA KELAS V SD NEGERI 216 PALEMBANG - Nurhaliza, Dinda; Hodsay, Zahrudin; Pratama, Aldora (Faculty of Teacher Training and Education, 2025)
This research aims to determine whether there is an influence of the Make A Match model on the motivation to learn Indonesian for class V at SD Negeri 216 Palembang. This research uses a Quasi Experimental research method with the Nonequivalent Control Group. In this study, class V A with a total of 25 students was the experimental class, while class V B with a total of 25 students was the control class. The data collection techniques used in this research activity are questionnaires and documentation. The data analysis technique used is the Independent Simple T-test. In the posttest results of the control class and experimental class which showed significant differences after implementing the Make A Match learning model, analysis of the data obtained by T-count was 1.783 where the T-table was 1.677, so Ho was rejected and Ha was accepted. So, after testing SPPS.26, it can be concluded that there is a significant influence on the application of the Make A Match learning model on the science learning motivation of fifth grade students at SD Negeri 216 Palembang.